Perancangan Program Pembayaran Service Motor - Ida Darwati (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Payment systems that still use manual systems take longer and sometimes there is an error in the process of calculating the total cost, these things can be an obstacle in a payment process. Currently the development of computer technology has been increasingly rapid, so many companies are switching from manual system to computerized system, because it is expected with a computerized system can shorten a process and produce accurate information. Using computerized system in service payment can overcome the constraints that occur when still using the manual system.